Which South Africa was better during apartheid? (Alternate Horizons, 2024)
The phrase "things were better under apartheid" is one that has emerged from time to time. This phrase is uttered by older South Africans who feel let down by the governing party, which equally played a role in achieving democracy in South Africa. This highlights the need to examine what this phrase means and why it has been uttered, considering the history of South Africa and apartheid. This paper discusses this phrase by analysing two broad ideas reflected by it.